Appraisal of changing urban fabric for urban resilience planning: a case study of Kathmandu valley, Nepal - Shrestha, Kriti; Pramanik, Malay; Vilas Nitivattananon; Himanshu, Sushil Kumar; AIT Scholarships (Pathum Thani, Thailand : Asian Institute of Technology, 2023)
Urban fabric refers to the tangible elements of urban areas, such as cities and towns. It includes the buildings, streets, parks, and other elements that make up the cityscape. Urban resilience is the ability of a city to withstand and recover from shocks and stresses. This research study investigates the urban fabric and resilience of Kathmandu Valley, encompassing the districts of Kathmandu, Lalitpur, and Bhaktapur. The study assesses the urban fabric and its resilience using a mixed-methods approach, aiming to identify research gaps and propose a flexible assessment framework that offers new tools and approaches to foster resilience in Kathmandu Valley. The conceptual framework identifies the key factors and their relationship with the urban fabric. Spatial and statistical tools were used to explore the spatial dynamics and attributes of urban fabric in Kathmandu. The analysis revealed substantial changes in land use and land cover from 2011 to 2021, characterized by urban expansion in all directions from the city center. Rapid urbanization, population growth, and natural disasters were identified as influential factors driving these changes. Multicollinearity and OLS regression were used to identify various factors impacting Kathmandu's urban fabric, including transportation accessibility, immigration density, vegetation, agriculture, river density, and elevation. The research findings underscore the need for infrastructure improvements, green space preservation, and effective risk management to foster urban resilience. This research contributes to the understanding of urban resilience by providing valuable insights into the contributors to the urban fabric and proposing potential solutions. It also highlights the need for comprehensive urban planning, risk mitigation strategies, and investments in the social and economic fabric. The implications of these findings extend to urban planning and policymaking not only in Kathmandu Valley but also in other cities worldwide.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Urban Innovation and Sustainability
Thesis (M. Sc.) - Asian Institute of Technology, 2023
Keywords: Urban ecology -- Nepal -- Kathmandu; City planning -- Nepal -- Kathmandu; Resilience (Ecology) -- Nepal -- Kathmandu